Resist or perish! Understanding the mode of resistance among young DIY Indonesian musicians - Rahadianto Sutopo , Oki; Ragil Wibawanto, Gregorius; Aryo Lukisworo, Agustinus (Perfect Beat, 2021)
This article examines the practice of resistance among young DIY musicians in Yogyakarta, Indonesia in the context of the post-reform era. DIY young musicians negotiate how to provide for their everyday economic needs while also upholding their music genre’s spirit of resistance against market commodification. Lately, commodification not only comes from the music industry but also from the state through neoliberal-oriented creative economy policies. Music falls into the category of a creative sector and is seen as a product to boost economic growth. Based on our empirical data, young musicians resist this through DIY practices in their music scene. We show the struggle of young musicians to sustain their musical values of authenticity (otentisitas) and autonomy (kemandirian). Instead of viewing resistance as homogenous, we observed three modes of resistance: the rookie, the in-between, and the afficionado, based on their level of commitment to being a DIY careerist. Our research offers a real-world example of theories around popular music and youth studies based on the experiences of young Indonesian musicians.